Spontaneous Twin Pregnancy: A Challenging and Exceptional Scenario in a Patient on Maintenance Hemodialysis in Sub-Saharan Africa - Mahamat Maimouna; Hermine Menye Ebana Fouda; Victorine Nzana F.; Aristide Eric Tomta Nono; Isabelle Nkwelle Mekone; Peter Mbala; François Folefack Kaze; Gloria Ashuntantang (Case Reports in Nephrology and Dialysis, 2022)
Chronic hemodialysis is associated with reduced fertility. Hence, pregnancy remains rare, challenging, and deleterious when unplanned, especially in low-resource countries. Contraception and births are very important in these settings. Though the main modes of contraception have been proposed in the chronic kidney disease (CKD) population, contraception still remains challenging in patients on maintenance hemodialysis. Most doctors, however, overlook contraception because of the low fertility, high rate of amenorrhea, and low libido. Furthermore, patients are less receptive to contraceptive counseling either because of a high desire to give birth or due to amenorrhea and low libido. Management of unplanned pregnancies is therefore very challenging and a multidisciplinary approach is the rule; however, it does not guarantee a good prognosis for both the mother and child. Very few cases of multiple pregnancies without induction of ovulation have been reported in patients with severe renal failure, especially those on maintenance dialysis. A 32-year-old multiparous woman with end-stage kidney failure (ESKF) and a residual diuresis of 700 mL per day who had been on inadequate maintenance hemodialysis for 36 months, presented with abdominal distension, which was confirmed on abdominal ultrasound to be a twin pregnancy at 22 weeks of gestation. Thereafter, we intensified hemodialysis (3 sessions/week), managed hypertension and anemia. The obstetrical course was uneventful until the 25th week of gestation when she developed grade 3 (WHO) hypertension and peripheral fluid overload. At the 29th week, she had a spontaneous vaginal preterm delivery of 2 babies weighing 1,350 g and 1,000 g, with an Apgar score of 8 and 7, respectively. Babies, however, died on day 1 and day 5 postpartum, respectively, from respiratory distress and early neonatal infection. The evolution of the mother was uneventful as she continued with her hemodialysis sessions. Twin pregnancies are a rare and very high-risk condition in end-stage renal disease and require multidisciplinary management.